Light variations and modelling of the sdB HS 0705+6700 - Niarchos, P. G.; Gazeas, K. D.; Manimanis, V. N. (Interplay of Periodic, Cyclic and Stochastic Variability in Selected Areas of the H-R Diagram, 2003)
The first complete I-filter light curve of the eclipsing sdB binary HS 0705+6700 is analyzed using the Wilson-Devinney code and new geometric and photometric elements are derived. Using these elements together with the available spectroscopic data, it was possible to build a detailed model of the system. Our results are in good agreement with those found from photometric studies in other bands.